2017
DOI: 10.1071/an15441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical nociceptive threshold testing in Bos indicus bull calves

Abstract: Pain assessment in cattle is difficult, but is essential to assess the effect of surgery 13 and analgesic drugs. Nociceptive threshold testing is an objective pain assessment 14 tool that has not been described in Bos indicus cattle. A technique for mechanical 15 nociceptive threshold testing was developed for use in Bos indicus cattle undergoing 16 surgical castration to evaluate post-operative pain. 17 Abstract. 18The aim of this prospective, controlled, randomised trial was to develop a technique 19 for mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Some research studies investigating pain assessment showed a decrease in MNT when measured over consecutive days. Stubsjøen et al (2010) demonstrated a decrease in MNT in sheep over three consecutive days, and Musk et al (2017) found a decreased MNT in bull calves tested over six days [38]. In contrast, an increase in MNT measurements was observed in the current study.…”
Section: Discussioncontrasting
confidence: 62%
“…Some research studies investigating pain assessment showed a decrease in MNT when measured over consecutive days. Stubsjøen et al (2010) demonstrated a decrease in MNT in sheep over three consecutive days, and Musk et al (2017) found a decreased MNT in bull calves tested over six days [38]. In contrast, an increase in MNT measurements was observed in the current study.…”
Section: Discussioncontrasting
confidence: 62%
“…Objective assessments in this context are those that are measurable and consistent when different instruments are used to attain the measurement. For Bos indicus cattle undergoing castration, both objective and subjective assessments of pain and stress have been utilised [ 7 , 8 , 9 , 10 ]. Objective assessments of pain or inflammation include evaluation of changes in blood concentrations of circulating cortisol, haptoglobin, creatinine kinase, total protein, and packed cell volume, as well as nociceptive threshold testing, and changes in bodyweight and activity (using pedometry) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For Bos indicus cattle undergoing castration, both objective and subjective assessments of pain and stress have been utilised [ 7 , 8 , 9 , 10 ]. Objective assessments of pain or inflammation include evaluation of changes in blood concentrations of circulating cortisol, haptoglobin, creatinine kinase, total protein, and packed cell volume, as well as nociceptive threshold testing, and changes in bodyweight and activity (using pedometry) [ 8 , 9 , 10 ]. Other assessments in Bos indicus cattle following castration are based almost exclusively on the observation and the interpretation of behaviour, which are more challenging and time consuming to quantify, but may more accurately capture the animals’ response to the environment [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%